A comparative study between the Chrono-log 700 and the Sysmex CS-2100i analyzers for assessing ristocetin cofactor activity in patients with von Willebrand disease - Boulassel Mohamed-Rachid; Abdellatif Hussein; Al-Falahi Karima; Al-Hashmi Fatma; Bouchareb Yassine; Al-Abri Buthaina; Al-Jahdhami Habib (Journal of Laboratory Medicine)
A variety of methods are currently used to measure von Willebrand factor (VWF) activity, but still the VWF ristocetin cofactor (VWF:RCo) assay using the manual aggregometry technique is the reference method, even having high inter-laboratory variability. The automated coagulation analyzers offer several advantages for routine testing. Herein the performance of the automated Sysmex CS2000/2100i analyzer was compared to the manual aggregometer Chrono-log 700 for assessing VWF:Co activity in patients suspected of having von Willebrand disease (VWD).